Investigation of Galvanic Corrosion in Screw Down of Hot Aluminum Rolling Mill - Akbar Mottahedi, Ali (Asian Journal of Chemistry, 2010)
A complicated problem has been occured in screw down of hot aluminum rolling, in an aluminum rolling mill company. The subject was started as Maintenance Engineering Department stated that there are some inclusions in greases of screw down. After some theoretical, laboratory and practical research works with considering process, technology and environmental aspects, the problem was turned out to be galvanic corrosion. An innovational method was applied to reduce the cathodic area by painting and insulating accessories rolling machine (rolling tables), the corrosion of main machine in screw down stopped and the rolling mill was protected. In this paper the phenomena is fully characterized by scientific aspects of galvanic corrosion and applied in rolling mill technology.